1992
DOI: 10.1159/000243887
|View full text |Cite
|
Sign up to set email alerts
|

Growth Velocity of Some Fetal Parameters

Abstract: In this study, fetal growth velocities of the brain weight (whole brain and infratentorial part) and of the right and left fronto-occipital diameters were established from 420 normal fetuses and neonates. The age of the subjects ranged from 10 to 41 gestational weeks. Growth rates were computed by time intervals, and velocity curves were plotted with their 95% confidence intervals. The whole brain displays an accelerating pattern of growth until 35 weeks; thereafter, the growth rate breaks down. The growth vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 7 publications
1
6
0
2
Order By: Relevance
“…This is comparable with previous MR volumetric studies, performed on 3D reconstructed data within smaller gestational age ranges, which presented growth ranges of 10.22–17% (Clouchoux et al 2011; Rajagopalan et al 2011; Scott et al 2011). The volume range increased from around 30 weeks of gestation suggesting that individual variation starts to arise and becomes greater with progressing age as previously shown (Guihard-Costa and Larroche 1992; Scott et al 2011; Snijders and Nicolaides 1994). Cortical volume increased at a relative growth rate of 14.78% per week in our sub-cohort of fetuses.…”
Section: D Volumetric Measurementssupporting
confidence: 75%
See 2 more Smart Citations
“…This is comparable with previous MR volumetric studies, performed on 3D reconstructed data within smaller gestational age ranges, which presented growth ranges of 10.22–17% (Clouchoux et al 2011; Rajagopalan et al 2011; Scott et al 2011). The volume range increased from around 30 weeks of gestation suggesting that individual variation starts to arise and becomes greater with progressing age as previously shown (Guihard-Costa and Larroche 1992; Scott et al 2011; Snijders and Nicolaides 1994). Cortical volume increased at a relative growth rate of 14.78% per week in our sub-cohort of fetuses.…”
Section: D Volumetric Measurementssupporting
confidence: 75%
“…The supratentorial brain tissue followed a quadratic growth pattern indicating accelerated growth at this stage of development as demonstrated by the increasing growth velocity in brain weight in the third trimester (Guihard-Costa and Larroche 1992). The absolute volume increased between 22 and 38 weeks at a relative growth rate of 13.04% per week.…”
Section: D Volumetric Measurementsmentioning
confidence: 96%
See 1 more Smart Citation
“…3D ultrasonography [14, 31] estimated an accelerating trajectory through 20 to 30 GW, as was shown in the present study. Further, a study of brain weight found that growth velocity of the infratentorial part of the brain (including the cerebellum) increased between 20 and 35 GW, after which the rate plateaued until term [4]. …”
Section: Discussionmentioning
confidence: 99%
“…In the later half of gestation, the human brain grows and increases in structural complexity at a more rapid rate than in any other period of development [1–4]. The cerebellar cortex is undergoing extensive foliation leading to accelerating increases in surface area [5, 6].…”
Section: Introductionmentioning
confidence: 99%